If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(2x + -3) = x + 26 Reorder the terms: (2 + x)(2x + -3) = x + 26 Reorder the terms: (2 + x)(-3 + 2x) = x + 26 Multiply (2 + x) * (-3 + 2x) (2(-3 + 2x) + x(-3 + 2x)) = x + 26 ((-3 * 2 + 2x * 2) + x(-3 + 2x)) = x + 26 ((-6 + 4x) + x(-3 + 2x)) = x + 26 (-6 + 4x + (-3 * x + 2x * x)) = x + 26 (-6 + 4x + (-3x + 2x2)) = x + 26 Combine like terms: 4x + -3x = 1x (-6 + 1x + 2x2) = x + 26 Reorder the terms: -6 + 1x + 2x2 = 26 + x Solving -6 + 1x + 2x2 = 26 + x Solving for variable 'x'. Reorder the terms: -6 + -26 + 1x + -1x + 2x2 = 26 + x + -26 + -1x Combine like terms: -6 + -26 = -32 -32 + 1x + -1x + 2x2 = 26 + x + -26 + -1x Combine like terms: 1x + -1x = 0 -32 + 0 + 2x2 = 26 + x + -26 + -1x -32 + 2x2 = 26 + x + -26 + -1x Reorder the terms: -32 + 2x2 = 26 + -26 + x + -1x Combine like terms: 26 + -26 = 0 -32 + 2x2 = 0 + x + -1x -32 + 2x2 = x + -1x Combine like terms: x + -1x = 0 -32 + 2x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-16 + x2) = 0 Factor a difference between two squares. 2((4 + x)(-4 + x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(4 + x)' equal to zero and attempt to solve: Simplifying 4 + x = 0 Solving 4 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + x = 0 + -4 x = 0 + -4 Combine like terms: 0 + -4 = -4 x = -4 Simplifying x = -4Subproblem 2
Set the factor '(-4 + x)' equal to zero and attempt to solve: Simplifying -4 + x = 0 Solving -4 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + x = 0 + 4 x = 0 + 4 Combine like terms: 0 + 4 = 4 x = 4 Simplifying x = 4Solution
x = {-4, 4}
| A=M(1+rt) | | http://mathsonline.com.au/assets/interactives/images/3244-116-2.png | | factor-16x^2+34x-18= | | 0.9x-0.1(10-2x)=-0.4(x-5) | | 10-8x=10x+1 | | 8-(-3x-2)= | | 8-(-3x-1)= | | x^2-3000x+1600=0 | | -17=14x-6/-12 | | -4*(5-x)+(3-x)*(4-x)*(5-X)-4*(3-X)=0 | | 3x-6(6x-15)=-9 | | 5+x=-10+7 | | -4(5-x)+(3-x)(4-x)(5-X)-4(3-X)=0 | | -3.3x=-29.7 | | -182=6x-4(3x+29) | | ft(-4)=3x^2+7 | | 3-2(2x-4)=3x-4 | | x+.15x=1500 | | 0.6+7.9=4.6 | | f(x)=3x^2+7 | | 8x^2-53-21=0 | | 15x^2+25xy-45xz=0 | | x+x+23+23= | | 8a+5b=44 | | 4x+24=23 | | -5x+3(-6x+8)=-252 | | 10msquared= | | 3(2-3x)=2(-4x+7) | | exp(-0.1X^2)= | | 9/10-4/10= | | 2/5(x-9/40=3/10(7-2x) | | 2p+x+4p= |